Bureau Of Mines Mineral Investigations In The Juneau Mining District, Alaska, 1984-1988 - Volume 2.- Detailed Mine, Prospect, And Mineral Occurrence Descriptions - Introduction (The National Institute for Occupational Safety and Health (NIOSH), 2012)
This publication summarizes the Bureau's activities as part of a study of the Juneau Mining District (JMD) during the period 1984-1988. The objectives of the program were to identify the type, amount, and distribution of mineral deposits in the district, determine ore reserves, study beneficiation technologies for the ore, make feasibility studies, and address economic and legislative effects on mineral development. The JMD study was a cooperative study involving the Bureau and the Alaska Division of Geological and Geophysical Surveys (ADGGS). Over 30 employee-years were spent by the Bureau on this project. Bureau investigations in the JMD consisted of a district-wide investigation of industrial materials in addition to site-specific investigations of precious and base metals in five subareas. During the 4 years of the JMD study, more than 300 areas, mines, prospects, and occurrences were visited, which contain gold, silver, copper, zinc, lead, nickel, cobalt, tungsten, molybdenum, chromium, and platinum group metals (PGM). More than 59,000 feet of underground workings were mapped and sampled. More than 5,500 samples were taken; one diamond drilling program and three geophysical surveys were completed. An up-to-date and complete mineral data base for the JMD did not exist prior to this study. The JMD study, which coincided with a tremendous increase in mineral interest and activity in the district, has proven to be valuable to both the minerals industry and land management agencies. The discovery of two new mineral occurrences and compilation of data on known mines, prospects, and occurrences have aided industry activity in the region. The study enabled timely data to be available to land management agencies at the Federal, State, and municipal levels.